TRANSITIONING FROM TRADITIONAL CLASSROOM TO NEW NORMAL EDUCATION SET-UP: A TEACHER PERSPECTIVE - Jessa T. Plaras; Roel P. Villocino (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Transitioning from traditional classroom to new normal set-up in education had greatly impacted education especially the teachers. Herewith, this study aimed to know the perspectives of teachers in the transitioning from traditional classroom to new normal education set-up. Hence, this qualitative phenomenological research study explored the perspectives of the teachers of Mawab Central Elementary School SPED Center and Assumption Academy of Mawab, Inc. The purpose of this study is to explore on teachers’ experiences, challenges, coping mechanisms, insights, suggestions, and recommendations of teachers in the abrupt transition from traditional classroom to new normal education set-up. There were 10 purposively selected teachers who participated in the conduct of the study, five participants from public and another five from private school. Learning in the new normal presented obstacles and difficulties for teachers, according to the findings. They were able to showcase their flexibility and resiliency in dealing with the change. As a result of the pandemic, the study also found out that teachers were able to gain new skills, come up with new ideas, and improve their own creativity and adaptability to address challenges brought by the pandemic. The study concluded with recommendations for the best programs that could help teachers deal with adversity, as well as areas for further research.